Sosialisasi Cara Pencegahan Stunting Di Kelurahan Dodu Wilayah Kerja Puskesmas Rasana’e Timur Kota Bima - Nini Niatullah Aliyati; Erni Faturahmah (Compromise Journal Community Proffesional Service Journal, 2024)
Stunting is a state of stunted growth experienced by children from the first 1000 days of life of life. It can also be explained as a growth problem that occurs in children under five years of age caused by chronic malnutrition, resulting in delays in the growth process. (under 5 years of age) caused by chronic malnutrition, which results in delays in the growth process. The purpose of this community service is to provide education to the community, youth, and village government on how to prevent and reduce the level of stunting effectively through health socialization efforts. effectively through health socialization efforts. The method used in this research is a qualitative descriptive approach. The results and objectives to be achieved from this activity are the residents of Dodu Village who have high enthusiasm, so that counseling activities run and the residents of Dodu Village became more aware of the ways to prevent stunting.